Havoc : a Deviants novel - Sampson, Jeff, 1982- (Sampson, Jeff, 1982- Deviants novel., 2012)
After genetic engineering endows sixteen-year-old Emily and her friends with super powers and changes them into werewolves, the teenagers set off on a dangerous mission to find the people who made them what they are, and to discover why.